Playing the Game: Leopold II's Foundation of the Congo Free State - Frank, Ryan (My University, 2009)
In this paper the author analyzes how King Leopold II received support for the International Africa Association in the United States and Europe. More specifically, the author will determine whether Leopold gained his support through persuasion or deception. The first chapter contains documents from scientists, philosophers and governmental agencies during the Victorian era, and argues that western ethnocentrism gave rise to "White Man's Burden" (defined as bringing western civilization to the rest of the globe in this paper), and that colonial governments used spreading civilization as justification for using the "inferior races" for their benefit. The second chapter provides a brief overview of the events leading up to and including the Berlin Conference, and identifies the significant occurrences that allowed Leopold II to obtain sovereignty of the Congo. In the third and final chapter, the author analyzes these key events, and debates whether Leopold was successful due to his humanitarian appeal or my means of deception. The author concludes that Leopold gained the Congo from deception and not persuasive techniques.
Keywords: Berlin West Africa Conference (1884-1885); Congo (Democratic Republic)--History--To 1908.; Congo (Democratic Republic)--Politics and government.; Association Internationale Africaine.; Leopold II, King of the Belgians, 1835-1909.; Sovereignty.